How are UK Academics Engaging the Public with their Research? A Cross‐Disciplinary Perspective. (24th February 2016) - Chikoore, Lesley; Probets, Steve; Fry, Jenny; Creaser, Claire
Abstract: This paper takes a cross‐disciplinary perspective in examining the views and practices of public engagement with research by UK academics. Using a mixed method approach consisting of a survey questionnaire and interviews, the paper identifies the range of audience groups that can potentially be engaged with by academics, and shows that some audiences are more relevant to particular disciplinary groups than others. The paper also identifies the various public engagement activities undertaken by academics and finds that some academics are using creative ways of engaging the public, such as using the services of public relations firms to help in disseminating their research in traditional media outlets, and also by using social media. Essentially, the study reveals that some academics feel the pressure of engaging particular audiences at the expense of those that are relevant to them and that, academics in the main, are opposed to the notion of mandating public engagement as part of appraisal systems.